2012
DOI: 10.1186/1475-2891-11-75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of folate intake on health outcomes in pregnancy: a systematic review and meta-analysis on birth weight, placental weight and length of gestation

Abstract: The beneficial effect of folic acid supplementation before and shortly after conception is well recognized, whereas the effect of supplementation during the second and third trimesters is controversial and poorly documented. Our aims were to systematically review randomized controlled trials (RCTs) investigating the effect of folate supplementation on birth weight, placental weight and length of gestation and to assess the dose–response relationship between folate intake (folic acid plus dietary folate) and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
2
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 40 publications
3
87
2
12
Order By: Relevance
“…Moreover, maternal serum folic acid level showed insignificant differences between group A and B (9.57 ± 3.63 vs. 9.1 ± 2.73 respectively, P = 0.27), which contradicts other previous studies as [12] [36] [43]. A systematic review done by Fekete et al [44] showed two-fold increase in folate intake in early pregnancy is associated with 2% increase in birth weight, which is a slight but significant increase. Therefore, Open Journal of Obstetrics and Gynecology vitamin B12 and/or folic acid deficiency is likely to affect methylation pathway of homocysteine to methionine which represents a crucial part of the one-carbon metabolism for synthesis of DNA, and RNA.…”
Section: Discussioncontrasting
confidence: 52%
“…Moreover, maternal serum folic acid level showed insignificant differences between group A and B (9.57 ± 3.63 vs. 9.1 ± 2.73 respectively, P = 0.27), which contradicts other previous studies as [12] [36] [43]. A systematic review done by Fekete et al [44] showed two-fold increase in folate intake in early pregnancy is associated with 2% increase in birth weight, which is a slight but significant increase. Therefore, Open Journal of Obstetrics and Gynecology vitamin B12 and/or folic acid deficiency is likely to affect methylation pathway of homocysteine to methionine which represents a crucial part of the one-carbon metabolism for synthesis of DNA, and RNA.…”
Section: Discussioncontrasting
confidence: 52%
“…However, no association of plasma folate, folate from food or folic acid from supplements was found with birth size (15). This result differed from the result of a systematic review and meta-analysis including eight randomized controlled studies, which indicated a 2% increase in infant birth weight for every two-fold increase in folate intake (94). No association between intake of total folate and preterm delivery was found in MoBa (33), which is in line with the mentioned systematic review and meta-analysis (94).…”
Section: Possible Explanations For Findings and Comparison With Othercontrasting
confidence: 73%
“…Thus, by the end of pregnancy, a woman may be at risk for folate deficiency. 34 Low maternal folic acid intake in pregnancy has been associated with increased risk of ASD. 35,36 High maternal BMI related to conception shortly after a previous birth has also been hypothesized to explain the link between short IPI and ASD risk.…”
Section: Discussionmentioning
confidence: 99%